2018
DOI: 10.1136/bmj.k2338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prostatic artery embolisation (PAE) versus transurethral resection of the prostate (TURP) for benign prostatic hyperplasia: randomised, open label, non-inferiority trial

Abstract: ObjectiveTo compare prostatic artery embolisation (PAE) with transurethral resection of the prostate (TURP) in the treatment of lower urinary tract symptoms secondary to benign prostatic hyperplasia in terms of patient reported and functional outcomes.DesignRandomised, open label, non-inferiority trial.SettingUrology and radiology departments of a Swiss tertiary care centre.Participants103 patients aged ≥40 years with refractory lower urinary tract symptoms secondary to benign prostatic hyperplasia were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
193
2
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(215 citation statements)
references
References 33 publications
4
193
2
16
Order By: Relevance
“…Nevertheless, PAE has come into use over the past years and was recently approved by the National Institute for Health and Care Excellence (NICE) as a minimally invasive approach for LUTS/BPH . Patient‐reported outcomes with PAE are similar to those for established surgical methods, and it has a better side‐effect profile but lower desobstructive efficacy . Because PAE is a very different therapeutic approach, outcome predictors for traditional transurethral surgical approaches are unlikely to be fully applicable to PAE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, PAE has come into use over the past years and was recently approved by the National Institute for Health and Care Excellence (NICE) as a minimally invasive approach for LUTS/BPH . Patient‐reported outcomes with PAE are similar to those for established surgical methods, and it has a better side‐effect profile but lower desobstructive efficacy . Because PAE is a very different therapeutic approach, outcome predictors for traditional transurethral surgical approaches are unlikely to be fully applicable to PAE.…”
Section: Introductionmentioning
confidence: 99%
“…Outcome predictors of PAE have barely been investigated and conflicting results require elucidation. The aim of the present study was to assess the variability of treatment outcomes in a patient cohort undergoing PAE within a randomized, open‐label, non‐inferiority trial and to identify patient characteristics and findings related to the intervention that might allow improved patient selection and early estimation of PAE outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The recent UK Register of Prostatic Embolisation (ROPE) study has shown its preliminary safety and efficacy in a multicentre observational evaluation, which also included an indirect comparison with TURP 3. This study follows other small randomised controlled trials suggesting some benefit of PAE over TURP,4 and in a linked article (doi:10.1136/bmj.k2338), a larger trial adds further detail to PAE’s ongoing evaluation 5…”
mentioning
confidence: 82%
“…In their randomised, open label non-inferiority trial,5 Abt and colleagues included 103 men (48 receiving PAE and 51 receiving standard TURP) with moderate benign prostatic hyperplasia (mean gland size 50 mL), who were followed up for a limited 12 week period after their assigned treatment. The primary endpoint was change in international prostate symptom score (IPSS).…”
mentioning
confidence: 99%
See 1 more Smart Citation